Sampling experience in a cherry plantation - Polyák, N. I.; Csizmazia, Z.; Vaszily, B.; Ancza, E.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2011)
Experiments in a cherry plantation were performed to find out that samples taken from various parts of the foliage of the tree what extent represent the whole tree. One tree from three different cherry varieties was selected. In the selection, we tried to form a good representation of the foliage of the orchard. 8 sampling locations were designated on each tree, in two different heights and four different directions according to the points of the compass.We measured the main sizes of the fruits in three orthogonal dimensions with a digital slide gauge with an accuracy of 0.01 mm; the mass of each cherry by an analytical balance, with an accuracy of 0.001 g; the mass of the stones with the same analytical balance, and then calculated the stone-pulp ratio. The measured and calculated data are used to characterize the sample in question.